2010
DOI: 10.3126/aej.v11i0.3651
|View full text |Cite
|
Sign up to set email alerts
|

Total Bacterial Counts of Raw Milk in Eastern Terai of Nepal

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
5
2
2
Order By: Relevance
“…Additionally, higher prevalence rates might be due to unhygienic processing, improper cleaning, deficient handling, and contamination of utensils. In contrast, our result was lesser than the findings of former studies by Acharya et al (2017), Dahal et al (2010), Aaku et al (2004), Mwangi et al (2000), Moustafa et al (1988) and Mohamed & El Zubeir (2007) who found the average value of 104.71×10 5 CFU/ml, 107 CFU/ml, 107×10 6 CFU/ml, 1×10 9 CFU/ml and 5.63×10 9 CFU/ml respectively. The differences in findings of these studies can be correlated to difference in time as well as place.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…Additionally, higher prevalence rates might be due to unhygienic processing, improper cleaning, deficient handling, and contamination of utensils. In contrast, our result was lesser than the findings of former studies by Acharya et al (2017), Dahal et al (2010), Aaku et al (2004), Mwangi et al (2000), Moustafa et al (1988) and Mohamed & El Zubeir (2007) who found the average value of 104.71×10 5 CFU/ml, 107 CFU/ml, 107×10 6 CFU/ml, 1×10 9 CFU/ml and 5.63×10 9 CFU/ml respectively. The differences in findings of these studies can be correlated to difference in time as well as place.…”
Section: Resultscontrasting
confidence: 89%
“…The average Total Viable Count (TVC) of pasteurized and raw milk was 15×10 4 CFU/ml and 59×10 5 CFU/ml respectively. Likewise, the TVC of raw milk in our study was higher than findings of some former studies in Nepal by Dhungel et al (2019) and Dahal et al (2010), in Ethiopia by Tassew & Seifu (2011), in India by Jain & Shreevastav (2014) and in Morocco by Belbachir et al (2015) who reported average plate count of 15×10 4 CFU/ml, 9.03×10 5 CFU/ml, 3.95×10 6 CFU/ml, 2.34×10 6 CFU/ml and 1.4×10 6 CFU/ml respectively. The reason behind the higher occurrence rate could be related to the difference in time, place and season of research.…”
Section: Resultscontrasting
confidence: 78%
“…Bacterial growth in milk is most rapid after 2-3 hours post milking when they enter the log phase of rapid growth [33]. In a study conducted on the microbiological quality of milk in a region of Nepal by reference [34], the high total bacterial count was attributed to the distance between the milk collection units and the milk plants. It was also noted that some of the milk transporters took long time to transport milk to the cooling center.…”
Section: Goodmentioning
confidence: 99%
“…Numerous pathogenic microorganisms have been found in different food items along the value chain. The following disease-causing bacteria were commonly reported in the target countries: Salmonella spp., Escherichia coli, Klebsiella spp., Shigella spp., Citrobacter spp., Pseudomonas spp., Vibrio spp., Campylobacter spp., Listeria spp., Cryptosporidium, L. monocytogenes, Brucella spp., Coxiella burnetii, Proteus spp., Staphylococcus spp., and Bacillus cereus (Hempen et al, 2004;Dahal et al, 2010;Mersha et al, 2010;Kirk et al, 2014;Adugna et al, 2015;Abera et al, 2016;Atnafie et al, 2017;Markos et al, 2017;Mengistu et al, 2017;Bantawa et al, 2018;Dhungel et al, 2019;Kassahun and Wongiel, 2019;Keba et al, 2020;Kumar et al, 2020;Osti, 2020). The available sources indicate a trend toward increasing resistance rates among pathogens such as Escherichia coli, Shigella spp., Salmonella spp., and Staphylococcus aureus to commonly prescribed antibiotics, including ampicillin, amoxicillin, penicillin, tetracycline, and trimethoprim/sulfamethoxazole (Tesfaw et al, 2013;Dulo et al, 2015;Garedew et al, 2015;Ejo et al, 2016;Assefa and Bihon, 2018).…”
Section: Microbial Contamination Of Foodmentioning
confidence: 99%